2018
DOI: 10.1017/s0950268818002212
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics of asymptomatic Norovirus infection in a population from oyster (Ostrea rivularis Gould) farms in southern China

Abstract: The following paper investigates the prevalence and characteristics of asymptomatic norovirus infection in the population living around oyster farm sites. Two consecutive surveys were conducted from January 2014 to December 2014 and 4549 stool samples were screened during the same time period. The total asymptomatic infection rate was 4.04% (184/4549). Norovirus infection rate was 5.20% in oyster farming population which was significantly higher compared with non-farming population where the infection rate was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The total infection rate of asymptomatic infected persons was 4.04%, and the incidence rate of NoV-infected cultured oyster population was 5.20%. The genotypes were diverse, GI.2, GI.3, GI.5, GI.6, GI.8, GII.3, GII.4, GII.5, GII.6, GII.8, GII.13, and GII.17 ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The total infection rate of asymptomatic infected persons was 4.04%, and the incidence rate of NoV-infected cultured oyster population was 5.20%. The genotypes were diverse, GI.2, GI.3, GI.5, GI.6, GI.8, GII.3, GII.4, GII.5, GII.6, GII.8, GII.13, and GII.17 ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study identified GII.4 as the most common genotype in asymptomatic individuals. The predominance of GII.4 in asymptomatic individuals has been reported in Tanzanian and American Indian children ( Grant et al., 2017 ; Moyo et al., 2014 ), while the dominance of non-GII.4 genotypes in asymptomatic individuals has also been reported in other countries ( Wang et al., 2018 ; Bucardo et al., 2017 ; Utsumi et al., 2017 ; Koo et al., 2016 ). These findings suggest that genotype distributions in symptomatic and asymptomatic individuals vary depending on the setting or country.…”
Section: Introductionmentioning
confidence: 84%
“…Compared to GI.3, GI.9 gained a high affinity to non-secretors, but lower affinities to A and AB, which could be explained by the two mutations at the binding interface and the surrounding area. To our knowledge, the binding feature of GI.9 is firstly characterized and it shows broad-spectrum affinity to all HBGA phenotypes, which partly explain GI.9 as the highest asymptomatic NoV infection in Changsha Bay farm sites ( Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The P domain encoding sequences were cloned into T-vectors (Thermo Fisher, United States). The resulting variant fragments were GI.3 (the outbreak strain), GI.9 (extracted from stool sample provided by Guangdong CDC) ( Wang et al, 2018 ) and GI.2 (accession number KF306212 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation